Indistinguishability: Diverse examples depict how indistinguishability plays a central role in computer science. - ATTIYA, HAGIT; RAJSBAUM, SERGIO (Communications of the ACM, 2020)
The article considers how indistinguishability is central to the abstraction and interaction inherent to computer science, and gives four specific examples of this phenomena in which components of a program lack knowledge or awareness of other components. It notes the topological nature of indistinguishability and reports it is often the source of lower bounds and impossibility reports.